Double Balanced Quadrature Subharmonic Cmos Mixer For WCDMA Direct Conversion Receiver - Mohd Resali, Mohd Sofwan (Universiti Sains Malaysia, 2005)
This report describes a sub-harmonic mixer for WCDMA applications. The circuit converts a 2GHz RF signal directly to baseband using a 1GHz LO frequency. The mixer operates in the quadrature double-balanced mode and requires octet-phase (0' , 45', 90' , 135' , 180' , 225' , 270' , and 315' ) local oscillator (LO). However the design of the octet-phase LO is not in the scope of this project. In this project, the inputs representing the LO signals are obtained from the generators. For linearity improvement, predistortion compensation and negative feedback scheme are used in the frequency down-conversion circuits. The mixer achieves a conversion gain of 2dB, 3.69-dBm IIP3,0.69dBm P1dB in the WCDMA Rx band (2110-2170 MHz). The performance has been verified using SpectreRF simulation.